Decompression of a Large Periapical Lesion: A Case Report of 4-Year Follow-Up - Claudio Maniglia-Ferreira; Fabio de Almeida Gomes; Marcelo de Morais Vitoriano; Francisco de Assis Silva Lima (Case Reports in Medicine)
This case report described the endodontic treatment and decompression of an extensive lesion in the anterior region of the mandible, detected during clinical and radiographic examination, in a patient with a complaint of slight tenderness to palpation in the area of mandibular right lateral incisor and canine. These teeth had been accessed without proper clinical evaluation, and their pulp tissues were exposed. The periodontal tissues were healthy, with no signs of inflammation or fistula. On radiographic examination, a radiolucent lesion with well-defined borders was seen extending from the distal root of mandibular left second premolar to the mesial root of mandibular right second premolar. Central and lateral mandibular left incisors were unresponsive to thermal pulp testing and exhibited coronal discoloration, consistent with a diagnosis of pulp necrosis. Due to persistent discharge from the root canal system during endodontic procedures despite application of intracanal medicament (calcium hydroxide paste), the decision was made to biopsy and decompress the lesion and conclude endodontic treatment. Histopathologic examination revealed a periapical granuloma. After endodontic treatment of the involved teeth, at 4-year clinical and radiographic follow-up, the affected region was almost completely repaired.